Laboratory study of H2SO4/H2O nucleation using a new technique – a laminar co-flow tube. Issue 1 (1st January 2018) - Trávníčková, Tereza; Škrabalová, Lenka; Havlica, Jaromir; Krejčí, Petr; Hrubý, Jan; Ždímal, Vladimír
Abstract: Nucleation of aerosol particles from gaseous precursors is an important stage in the formation of atmospheric secondary aerosols or in industrial applications, particularly coal burning boilers. We introduce a novel laboratory device for studying binary or ternary nucleation – a laminar co-flow tube (LCFT) – and provide first data for the H2 SO4 /H2 O system, showing that LCFT is able to cover a wide range of nucleation rates. The experimental set-up and the underlying transport processes are explained. Advantages of LCFT over methods employing turbulent mixing are suppression of wall losses and an accurate mathematical model. The determined nucleation rates are by about two orders of magnitude lower than typical literature values. Results of various nucleation experiments often show systematic differences unexplained by the present level of knowledge. Introduction of the LCFT technique based on a well-defined laminar diffusion process may help to identify the method-related biases.